Attraverso musei di celluloide: rovesciare lo sguardo (ACME, 2021)
In the age of immersive and digital cinematic experience, does it still make sense to talk about two black & white 70-years-old short films, that were conceived to reach - and, perhaps, to educate - the widest audience possible? Carpaccio and Caravaggio, by Umberto Barbaro and Roberto Longhi, were produced between 1947 and 1948, in the midst of the Italian Reconstruction. They are two exemplary pieces of a potential chapter of post-war Italian cinema - which would later take different paths, with other political and theoretical lines taking hold - and not simply the fruits of the whim of a great art historian and superb writer supported by a cultured and resourceful friend working in cinema industry. The two films are discussed in the context of the “cinema corto” of the 40s and 50s. Furthermore, the relationship between the artwork and its audience will be taken into account by comparing these short movies with a later Soviet film, Vzgljanitje na litso (1966), by Pavel Kogan, which in turn deals with the reactions of museum visitors in front of the leonardesque Madonna Litta, moving the gaze of the camera towards the viewers, opening to a reverse angle of the work of art which is perhaps similar to the one imagined by Barbaro and Longhi.